Effect of acupuncture pretreatment on clinical pregnancy rate in women with diminished ovarian reserve undergoing IVF-ET: study protocol for a multicenter randomized controlled trial - Liu, Xin; Su, Chenchen; Li, Junmin; Chen, Li; Zhang, Qinhua; Sun, Yan; Xu, Jinbang; Zhang, Cuilian; Cheng, Xinjie; Li, Xuemei; Yang, Huisheng; Xie, Yicong; et al. (Frontiers in Endocrinology, 2026)
IntroductionDiminished ovarian reserve (DOR) is known to reduce the likelihood of achieving pregnancy or live births in women undergoing in vitro fertilization and embryo transfer (IVF-ET). Acupuncture maybe effective for DOR, but current evidence remains limited and inconclusive.Methods and analysisThis study is a multicenter, randomized, placebo-controlled trial conducted on a large scale. A total of 300 women with DOR preparing for IVF-ET will be randomized 1:1 to acupuncture or placebo acupuncture. Interventions will be administered from the second menstrual cycle preceding the IVF cycle until the day of oocyte retrieval. The primary outcome is the clinical pregnancy rate (CPR) following the first embryo transfer. Secondary outcomes include various IVF-ET indicators, such as the number of follicles ≥ 14 mm, estradiol (E2) levels, and endometrial thickness on the day of human chorionic gonadotropin (hCG) administration; the number of retrieved oocytes, metaphase II (MII) oocytes, and two pronuclei (2PN) fertilizations; as well as the rates of 2PN fertilization, available embryos, high-quality embryos, implantation, cycle cancellation, biochemical pregnancy, pregnancy loss, sustained pregnancy, and live birth. Additionally, ovarian reserve indicators—including antral follicle count (AFC), basal serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and E2, and anti-Müllerian hormone (AMH)—along with scores from the Self-Rating Anxiety Scale (SAS) will also be evaluated.Ethics and disseminationThe trial has been approved by the ethics committees of all participating centers. The results will be disseminated in academic journals.Clinical Trial Registrationhttp://itmctr.ccebtcm.org.cn/, identifier ID: ITMCTR2024000021.